ОPTIMAL ALGORITHM OF COMPLEX PROCESSING OF INFORMATION ABOUT THE SPATIAL POSITION OF AEROLOGICAL RADIOSONDE - E. A. Bolelov; Yu. M. Ermoshenko (Научный вестник МГТУ ГА, 2016)
Methods of Markov theory of optimal stochastic processes estimation used for optimal aggregation of information about position of different objects can be successfully used in aerological radiosonde ascents problems. In this case, the aim is the integration of multi (functional, structural and information) into a single system of radar and navigation gauges spatial coordinates of aerological radiosonde. The need for the simultaneous measurement of the spatial coordinates of aerological radiosonde radar and radio navigation meter due to the fact that each of the meters does not meet all the requirements for accuracy and reliability of determining the spatial coordinates of aerological radiosonde. The problem of optimal algorithm synthesis of complex signal processing of satellite navigation systems GLONASS/GPS, relayed from the board and aerological radiosonde output aerological radar using the methods of Markov random processes, estimation theory is considered in this article. The synthesis is based on the solution of Stratonovich equation. In this article, a solution of Stratonovich was obtained for the case where the dynamics of the state vector in time is described by the quasi-random process.